2004
DOI: 10.1063/1.1825057
|View full text |Cite
|
Sign up to set email alerts
|

Artificial ferroelectricity in perovskite superlattices

Abstract: Evidence of short-range antiferroelectric local states in lanthanum-and titanium-modified Sr 0.3 Ba 0.7 Nb 2 O 6 ferroelectric ceramics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 14 publications
4
38
0
Order By: Relevance
“…In a similar zirconate system of SrZrO 3 /SrTiO 3 , the compressive strain has been reported to result in ferroelectricity in its superlattices. 27 Theoretical calculations by first principle density functional theory indicate that such 5 strain induced polarization originates from a lattice distortion, which is characterized by a prediction that all the cations move towards the interface with the Zr 4+ exhibiting the largest relative displacement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar zirconate system of SrZrO 3 /SrTiO 3 , the compressive strain has been reported to result in ferroelectricity in its superlattices. 27 Theoretical calculations by first principle density functional theory indicate that such 5 strain induced polarization originates from a lattice distortion, which is characterized by a prediction that all the cations move towards the interface with the Zr 4+ exhibiting the largest relative displacement.…”
Section: Introductionmentioning
confidence: 99%
“…The deduced value of P CZO =2.3×10 13 e/cm 2 =3.5 μCcm -2 , is in good agreement with the experimentally determined values for a comparable compressively strained 40 uc SrZrO 3 /SrTiO 3 bilayer-heterostructure. 27 In short, the strain induced polarization model can fit well the critical thickness dependence of the sheet carrier density for CZO/STO heteostructures, and can explain largely the metallic conduction at the nonminally-nonpolar perovskite interface between the two band insulators, when the content of oxygen vacancies is negligible. It is noteworthy that the deduced polarization of P CZO =3.5 μCcm -2 in CZO/STO (t≤14 uc) is much lower than that expected at the polar LAO/STO interface, P LAO =e/2a LAO 2 =55.8 μCcm -2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 These studies highlighted the fact that three main factors govern the physics of multilayers: epitaxial strain, electrical boundary conditions, and interfacial effects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the artificial super lattice of BT/SrTiO 3 hetero-epitaxial thin films had an extremely high dielectric constant due to local lattice strain at the interfaces between BT and ST films. 8) Both results indicated that the local lattice strain was quite important for enhancing the dielectric properties. Figures 11(a) and 11(b) show cross-sectional TEMs of Pt/BT NC 3D-assemblies/Pt capacitors applied for a practical measurement and the schematic image, respectively.…”
Section: Origin Of the High Dielectric Properties Of Bt Nc 3d-assembliesmentioning
confidence: 60%